Yield of rice and its mineral contents as influenced by sewage sludge and nitrogen (Bangladesh Journal of Scientific Research, 2012)
Key words: Sewage sludge; Nitrogen fertilization; Rice grain yield; Mineral contentsDOI: http://dx.doi.org/10.3329/bjsr.v24i2.10774 Bangladesh J. Sci. Res. 24(2):161-168, 2011 (December)